(untitled) (Applied Biological Research, 2012)
A study was conducted by collecting data from 60 commercial layer farms (15 farms in deep litter system, 25 farms in cage system and 20 farms in cages on elevated platform system) to assess the influence of housing system on production performance of commercial layers. The overall hen day egg production (21-72 weeks) was significantly higher in conventional cage system (78.85±0.70) and cages on elevated platform system (80.15±1.19) comparedtodeep litter systemof rearing(72.41± 0.51). The system of rearing had significant influence on feed efficiency for each production period as well as full production period. The values were 1.66 ± 0.02, 1.63 ± 0.02 and 1.86 ± 0.02 in conventional cages, cages on elevated platform and deep litter system of rearing, respectively. The feed consumption was significantly higher in deep litter system in comparison to other two rearing systems. The livability was significantly lower in deep litter system of rearing (85.94 ± 0.36) than conventional cage system (89.32 ± 0.90) and cages on elevated platform system (89.39 ± 1.08).